ИСПОЛЬЗОВАНИЯ 3D-ТЕХНОЛОГИЙ ПРИ ПРОВЕДЕНИИ ЗАНЯТИЙ ПО ПРЕДМЕТАМ: «АНАТОМИЯ И ФИЗИОЛОГИЯ ЧЕЛОВЕКА» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article aims to improve the teaching methods of «Human Anatomy» and «Age Anatomy» disciplines in comprehensively conducting professional and specialized research in the field of pedagogy at Naryn State University (NSU). The article paid special attention to the subject of human anatomy and the connection of IT technology. The possibility of an instructional demonstration (publication) of human anatomy based on a three-dimensional graph in the field of education was considered. At the same 191 time, the use and possibilities of 3D modeling with the help of Ultimaker Cura software were considered in the teaching process.
Keywords: anatomy, skeleton, model, body structure, 3D modeling, slicer, IT technology, demonstration, interactive whiteboard, prototyping.